Eurobonds: The blue bond concept and its implications - Jaques Delpla; Jakob von Weizsäcker (Bruegel, 2011)
The Blue Bond proposal, published in May 2010 (Bruegel Policy Brief 2010/03) suggests that sovereign debt in euro-area countries be split into two parts. The first part, the senior Blue tranche of up to 60 percent of GDP, would be pooled among participating countries and jointly and severally guaranteed. The second part, the junior Red tranche, would keep debt in excess of 60 percent of GDP as a purely national responsibility. This paper revisits the proposal, discusses its implications and addresses some of the comments and criticisms received in response to the proposal. This paper was prepared for the European Parliament's Economic and Monetary Affairs Committee, session of 21 March 2011 on the interaction between bank and sovereign debt resolution. Copyright remains with the European Parliament at all times.
Keywords: 330